Entre « parallélisme » et « intégrationnisme » : la négociation du parcours scolaire des Inuit du Nunavik - Marise Lachapelle (Les éditions de la Maison des sciences de l’Homme, 2016)
By establishing itself into the continuum of discussion between the “integrationist” and “parallelists” paradigms of aboriginal education, which was recently put forward by Widdowson and Howard, this article examines the everyday negotiations that operate the Nunavik Inuit who undertake post-secondary studies. These practices, which are not taken into account in school records, are just as indicative of student achievement and graduation rates, if not more, in addition to being revealing of their needs, aspirations and intentions throughout their journey. With this backdrop in mind, their experiences need to be better understood. This paper thus explores three aspects of the negotiation that Nunavik postsecondary students have to manage in order to nurture the discussions on Inuit education.